Responses of photosynthetic pigments in anabaena cylindrica to short term exposure of copper, cadmium, and lead - Wan Nurul Aisyah, Wan Jusoh; Wong, Ling Shing; Chai, Mee Kin (EM International, 2016)
The aquatic ecosystem has been disrupted due to the deposition of heavy metals from domestic and industrial sources. Some heavy metals are required in cell metabolism at low concentration, however, at higher concentration, these metals are lethal to the living cells. Conventional methods in detecting heavy metals in water have limitations. As alternatives, more economical and eco-friendly approaches such as bioindicators or biosensors are required to screen or detect heavy metals in the water. In this study, a cyanobacteria species, A. cylindrica was chosen as the potential bioindicator due to the ability of their photosynthetic pigments (chlorophyll and phycocyanin) to emit fluorescent when the cells were stressed. The percentage of change calculated could determine the degree of response of A. cylindrica towards Cu, Cd and Pb. Hence, the results from these studies confirmed that A. cylindrica showed responses to short-term exposure of Cu, Pb and were able to yield detectable fluorescent signals as short as 10 minutes after the exposure for all three metals. With further research and development, these pigments, showed a true potential for their applications in developing biosensors for the detection of heavy metals in drinking water.